3D Structural Dynamic Evaluation of AL-Arz Ice Cream factory - Mahde Soboh; Isalam Taqateq; Shaima Suliman; Tahreer Sabah (My University, 2014)
Al Arz ice cream factory lies in the eastern industrial zone, Nablus. The proposed design will be evaluated for resisting gravity loads as well as earthquakes. To make the mathematical model representative for the structure in reality, we need to analyze a 3D dynamic structural model for the building under static and dynamic loads. The analysis is verified using conceptual hand calculation for 1D model. Detailed design using manual and a software program will also be presented. Comparison between our conceptual analysis/design and the results from the software program will be high lightened. We expect the structural elements dimensions to be fine. However, we look forward to see the results of evaluation of proposed design by making comparison between 1D versus 3D analysis and between dynamic versus static design.